A influência do organofosforado clorpirifós no sistema vestibular de cobaias - Cogo, Lícia Assunção (2013)
Some chemicals have caused much damage to humans and the environment. Among these substances are chemical compounds like pesticides, often considered responsible for poisoning the workers, making it a public health problem. The aim of this study was to verify whether the organophosphate chlorpyrifos was influential in the vestibular system of guinea pigs in acute exposure. This was an experimental research. The research used 18 albino guinea pigs of the species Cavia porcellus, divided into three groups, with group I control the other, using distilled water and containing five animals. In Group II, six animals were administered 0.5 mg / kg / day of pesticide chlorpyrifos and group III, with seven animals at a dose of 1mg/kg/day of the same pesticide. The three groups were under experiment for 10 days. For analysis of the results was performed functional analysis of the vestibular system by electronystagmography (caloric test - with ice water) and histopathological analysis by scanning electron microscopy. The results showed no statistically significant difference for the variable frequency of appearance of nystagmus and angular velocity of the slow component in electronystagmography, and the number of ciliary tufts histologically by scanning electron microscopy. It was concluded that the organophosphate chlorpyrifos did not cause damage to the vestibular system of the guinea pigs at the doses tested in acute exposure.